Biofilm's Role in Chronic Cholesteatomatous Otitis Media: A Pilot Study. (May 2016) - Galli, Jacopo; Calò, Lea; Giuliani, Monica; Sergi, Bruno; Lucidi, Daniela; Meucci, Duino; Bassotti, Ezio; Sanguinetti, Maurizio; Paludetti, Gaetano
Cholesteatoma is a destructive lesion involving the temporal bone, which may induce severe complications due to its expansion and erosion of adjacent structures. Bacterial biofilm plays a crucial role in the pathogenesis of many otolaryngologic inflammatory/infectious chronic diseases. In this pilot study, we investigated, by means of cultural examination and with scanning electron microscope, the presence of bacterial biofilm in a series of samples from the epitympanic and mastoid region in patients affected by cholesteatoma and from the promontory region in patients with healthy mucosa who were undergoing to stapes surgery. The preliminary data support the association between biofilm and cholesteatoma (81.3% of the cases) and allow us to hypothesize that keratinized matrix of cholesteatoma may represent the ideal substrate for biofilm colonization and survival; this finding is consistent with the clinical course of aural cholesteatoma, characterized by recurrent exacerbations and recalcitrant course.